Molecular pharmacology of inflammation: Medicinal plants as anti-inflammatory agents. (January 2019) - Tasneem, Shumaila; Liu, Bin; Li, Bin; Choudhary, M. Iqbal; Wang, Wei
Graphical abstract: Abstract: Except for an essential step for the pathology of multiple diseases including atherosclerosis and rheumatoid arthritis, inflammation is an imperative therapeutic target for developing novel approaches for pharmacological interventions. Thus, molecular understanding of inflammation not only revealed the mechanisms of drug action and their biological targets but also has spawned innovative maneuvers to influence multifaceted biological systems, providing new prospects for drug designing and suggesting important new implications for existing clinical medicine. Meanwhile, modulation of inflammation with the use of medicinal plants proposed an alternate to conventional therapeutic strategies for numerous ailments, particularly when suppression of inflammation is expected. In modern literature, several species of medicinal plants have been shown substantial antiinflammatory and immunomodulatory actions including inhibitory effects on suppression of cellular and humoral immunity, lymphocyte activation, and propagation of apoptosis. Herein, we reviewed the molecular pharmacology of inflammation, chemical components and biological activities of medicinal plants such as, curcumin from Curcuma longa, and epigallocatechin-3-gallate from Camellia sinensis as well as their mechanism of action during inflammation at molecular level. An extensive review of the literature and electronic databases was conducted, encompassing PubMed, GoogleScholar, ScienceDirect, medlineplus, www.clinicaltrial.gov, www.fda.gov, www.ema.europa.eu, www.drugbank.ca, TrialBulletin.com, www.theplantlist.org, andwww.pharmacodia.com for assembling the information. Additionally, data was attained from books, ethnopharmacological literature, and relevant publications for essential elements of molecular mechanisms, signal transduction networks, transcription factors, complement system, reactive species, and clinical trials are selected for substantial understanding of biochemistry, pathophysiology as well as clinical importance of medicinal plants during inflammatory diseases.